A study on the protection of women against domestic violence in Pakistan : challenges and prospects - Dastagir, Ghulam (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2021)
Family violence is an expression of control and domination, to the core limit a women’s ability at homes. It halts making life choices which resulted in power imbalances. It is widely accepted that family violence often reflects the man’s desire to assert power and control over his partner. Rather than being perceived as a social problem, or a crime, it is usually accepted as a personal affair of the family and community that requires no intervention by the authority. The proponents of women's rights seek to eliminate systems of inequality and injustices in all aspects of women’s lives. Therefore, in addressing male violence, especially that is legitimised in the name of misconceived religious norms or so-called local traditions and culture, society must pay greater attention to these norms. Despite the overwhelming levels of intra-family violence against women, society and Pakistan’s law enforcement system maintain the perception that family violence is a private matter that requires neither government intervention nor criminal sanction. Moreover, Pakistan’s criminal justice system is designed primarily for violence between strangers which is not suited for the sensitivity and complexities of abusive family relationships. In this situation, the hypothesis is that there is an urgent need for a specific statute to deal with family violence, along with a specialised offence such as domestic violence as well as the modification of the current criminal justice procedures and its enforcement. To research family violence within the Pakistani context, this research has adopted the qualitative method of inquiry. Data were collected in a natural setting from lawmakers, sociologists, criminologists, family law lawyers, judges, academics, religious scholars, non-governmental organisations, police, and victims. Via direct interaction with the participants, which aids in understanding the complexities of human behaviour over an extended period, in-depth interviews were conducted. This research also analysed the data by adopting an inductive approach to thematically selected patterns to respond to the research questions. This research aims to develop a deep understanding of the central phenomenon through detailed description and thematic development, offering practical suggestions. The finding of this qualitative research is produced in this narrative report that will be proven to be rich in detail. The qualitative research findings showed that women still regarded as property in some sections of society. They are also subjected to outdated feudal and tribal customs in Pakistan since the society is patriarchal. Although the government is aware of the need for change, it has lack of courage to put it into action. This is proven by the absence of national domestic violence law and a gender-insensitive, as well as dysfunctional criminal justice system, which are significant factors in the state’s failure to protect women from endemic violence. This thesis recommends the changes in the criminal justice system to make it more sensitive and hence facilitate the needs of women. For instance, a specific statute to deal with family violence, along with a specialised offence of domestic violence and modified procedures to enforce it should be proposed to solve this issue. Violence against women cannot be eliminated unless the criminal justice system is made accessible, unbiased and effective enough to punish offenders and deal with victims with empathy. However, without involving the whole society, the laws cannot be implemented. Thus, there is a needs to modify and change the entire mindset of society.